A realidade do professor substituto nas universidades da região sul do Brasil: contribuições para a qualidade do trabalho docente - Aimi, Daniela da Silva (2010)
This study is part of the Research Line 1: Training, knowledge and professional development of the Graduate Program in Education of UFSM. The work presented has as main purpose to know the reality of a substitute teacher in the Federal Institutions of Higher Education in Southern Brazil, examining the possible contributions to the quality of teaching. This research is justified by the fact that studies of substitute teachers are few, these are temporary by the IES. But how are teachers of a higher education institution, are directly responsible for education and training provided to students. Thus, these can not be considered a category dissociated from the University, not being examined and studied in work on university education. It thus becomes necessary to the understanding of how these subjects constitute themselves as teachers within that context they remain inserted during the contract period. The methodological approach used for this study was quantitative and qualitative, considering that its use allows the development of different strategies for data analysis, whether based on principles of narrative analysis, either in statistical procedures. Participated in the first stage all substitute teachers employed during the years 2006 to 2008 of the federal Higher Education Institutions in Southern Brazil and the second, forty-five (45) teachers distributed within six (6) institutions surveyed. From the foregoing analysis, there is a general observation: these teachers are being built as teachers in relational dynamics, being able to produce knowledge, within relationships, often tense, built within the institution. In short, the substitute teacher, is constructed as a teacher from this experience and the basis for this construction is not only intellectually but also from his life story, consisting of emotional, affective, personal and interpersonal. Thus, it is beyond the vision teacher / object, because it is not just a guy who is put into an institution with a strict relationship of knowledge, information processing and "passes" to their students.